RNA therapeutics for cardiovascular disease. (May 2021) - Boada, Christian; Sukhovershin, Roman; Pettigrew, Roderic; Cooke, John P.
Abstract : Purpose of review: The development of mRNA vaccines against coronavirus disease 2019 has brought worldwide attention to the transformative potential of RNA-based therapeutics. The latter is essentially biological software that can be rapidly designed and generated, with an extensive catalog of applications. This review aims to highlight the mechanisms of action by which RNA-based drugs can affect specific gene targets and how RNA drugs can be employed to treat cardiovascular disease, with the focus on the therapeutics being evaluated in clinical trials. The recent advances in nanotechnology aiding the translation of such therapies into the clinic are also discussed. Recent findings: There is a growing body of studies demonstrating utility of RNA for targeting previously 'undruggable' pathways involved in development and progression of cardiovascular disease. Some challenges in RNA delivery have been overcome thanks to nanotechnology. There are several RNA-based drugs to treat hypercholesterolemia and myocardial infarction which are currently in clinical trials. Summary: RNA therapeutics is a rapidly emerging field of biotherapeutics based upon a powerful and versatile platform with a nearly unlimited capacity to address unmet clinical needs. These therapeutics are destined to change the standard of care for many diseases, including cardiovascular disease.